Comprehensive review and future perspectives on the photocatalytic hydrogen production - Corredor, Juan (2020)
ABSTRACT: Hydrogen represents a renewable energy alternative that may positively contribute to get over the global energy crisis while at the same time reducing its environmental burden. Overcoming the challenge of reaching this potential could be helped by careful choice of hydrogen (H-2) sources. Photocatalytic generation of H-2, although a minor alternative, appears to be a very good option at the time that liquid wastes are being degraded; therefore, this approach has given rise to an increasing number of interesting studies.Here, we aim to provide an integrated overview of the different photocatalytic, heterogeneous, homogeneous and hybrid systems. First, we categorize the units and mechanisms that take part in the photocatalytic process, and secondly we analyze their role and draw comparative conclusions. Thus, we analyze the role of (i) the electron source to carry out proton reduction, (ii) the proton source, which can be free protons in the medium or a proton donor compound, (iii) the catalyst nature and concentration, and (iv) the photosensitizer nature and concentration. We also provide an analysis of the influence of the solvent, especially in homogenous systems as well as the influence of pH. We provide a comparison of the photocatalytic performance, highlighting the advantages and disadvantages, of different systems. Thus, this review is, on the one hand, an update on the state of the art of photocatalytic generation of H-2 from a full perspective that integrates homogeneous, heterogeneous and hybrid systems, and, on the other, a source of useful information for future research.